1999
DOI: 10.1111/j.1469-7793.1999.0377v.x
|View full text |Cite
|
Sign up to set email alerts
|

Isoform‐specific regulation of the sodium pump by α‐ and β‐adrenergic agonists in the guinea‐pig ventricle

Abstract: 1. Guinea-pig ventricle was used in the RNase protection assays to determine which á-isoforms of the Na¤-K¤ pumps are present, and ventricular myocytes were used in whole cell patch clamp studies to investigate the actions of á-and â-adrenergic agonists on Na¤-K¤ pump current. 2. RNase protection assays showed that two isoforms of the á-subunit of the Na¤-K¤-ATPase are present in guinea-pig ventricle. The mRNA for the á1-isoform comprises 82% of the total pump message, the rest being the áµ-isoform. 3. We have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
44
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 20 publications
8
44
1
Order By: Relevance
“…Specifically, this inhibition is predominantly mediated by the novel PKC-δ isoform. Our results are consistent with those of Gao et al [4] , who demonstrated that I h was specifically regulated by PKC. However, in their study, I h was increased by α-adrenoceptor stimulation via the PKC pathway, which is not congruent with our result showing a PKC-δ-mediated decrease in I h .…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Specifically, this inhibition is predominantly mediated by the novel PKC-δ isoform. Our results are consistent with those of Gao et al [4] , who demonstrated that I h was specifically regulated by PKC. However, in their study, I h was increased by α-adrenoceptor stimulation via the PKC pathway, which is not congruent with our result showing a PKC-δ-mediated decrease in I h .…”
Section: Discussionsupporting
confidence: 83%
“…Numerous studies over the years have highlighted the isoform-specific modulation of Na + -K + pumps by transmitters or kinases in many types of cells [4,25,26] . In this study, we found that the α 2 -isoform Na + -K + pumps are specifically inhibited by adenosine.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations